Mixing γ-Al2O3, silica-ZIF-8 and activated carbon nanoparticles in aqueous N-methyldiethanolamine+sulfolane as a nanofluid for application on CO2 absorption - Mohammad Keshavarz Bahadori; Reza Golhosseini; Mohammad Shokouhi; Ali T. Zoghi (Journal of CO2 Utilization, 2024)
Mixing of Al2O3, superactive carbon (SAC), and Si-ZIF-8 nanoparticles in alkanol amine solvents with aqueous and hybrid context were used to study the absorption of carbon dioxide. Hybrid-based nanofluids composed of aqueous N- methyldiethanolamine (MDEA) + Sulfolane (SFL) + small amount of nano particles including-γ-Al2O3, Si-ZIF-8 and SAC in three concentrations levels, were prepared by weighting each components. The Zeta potential of suspensions was found thatγ-Al2O3, Si-ZIF-8 and super activated carbon is stable in aqueous solvents. Absorption measurements were performed using the static method at a temperature of T = 313.15 K, gas partial pressure ranges up to about 1.2 MPa, nanoparticle concentrations of 0.02 – 0.50 by weight percent, and fixed concentration of MDEA (40 wt%) and SFL (30 wt%). It was found that in the hybrid context (i.e., MDEA 40 wt% + SFL 30 wt%), the addition of γ-Al2O3 (0.1 wt%), Si-ZIF-8 (0.02 wt%) and SAC (0.1 wt%) has maximum effect on CO2 absorption. In aqueous context (i.e., MDEA 40 wt%), nanofluids used in the present study have no significant effect on CO2 capacity. The importance of the addition of SFL in nanofluids was discussed, and the experimental solubility data was modeled using Genetic Programming approach. Average absolute relative deviation (AARD), Coefficient of determination R2, as well as Root mean square error (RMSE) were 10.43% & 8.94%, 0.985 & 0.983, 0.051 & 0.054 for training and validating data, respectively. It is found that the determined parameters give satisfactory predictions in the modeling of the solubility.